2020
DOI: 10.1371/journal.pone.0238281
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and outcomes of a cohort of COVID-19 patients in the Province of Reggio Emilia, Italy

Abstract: ¶ Membership of the Reggio Emilia COVID-19 Working Group is provided in the Acknowledgments.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
84
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(102 citation statements)
references
References 23 publications
(31 reference statements)
11
84
1
3
Order By: Relevance
“…In this study, we assessed the clinical characteristics at the admission of patients with more severe infections admitted to our hospital in the first wave of the COVID-19 pandemic. The overall proportion of deaths was 32%, much higher than that observed in China [ 4 , 5 ], similar to that reported in other areas of Spain [ 6 , 7 , 8 ] and neighboring European countries [ 9 , 10 ], and lower than that reported in United States [ 11 ], for the same age ranges. The threshold of severity required for hospitalization could explain some of these differences, as too could the incomplete follow up of patients assessed in some studies.…”
Section: Discussionsupporting
confidence: 75%
“…In this study, we assessed the clinical characteristics at the admission of patients with more severe infections admitted to our hospital in the first wave of the COVID-19 pandemic. The overall proportion of deaths was 32%, much higher than that observed in China [ 4 , 5 ], similar to that reported in other areas of Spain [ 6 , 7 , 8 ] and neighboring European countries [ 9 , 10 ], and lower than that reported in United States [ 11 ], for the same age ranges. The threshold of severity required for hospitalization could explain some of these differences, as too could the incomplete follow up of patients assessed in some studies.…”
Section: Discussionsupporting
confidence: 75%
“…We found a J shaped relationship with BMI. Surprisingly, although strong associations of hypertension with COVID-19 have been reported elsewhere, 5 , 6 , 7 we found that people who developed fatal or critical care unit-treated COVID-19 had slightly lower blood pressures than those who did not, and that being on antihypertensives was associated with a lower risk than not being on any. Among the specific antihypertensive drug classes, thiazides and angiotensin 2 receptor antagonists or blockers had the lowest ORs.…”
Section: Discussioncontrasting
confidence: 65%
“…Initial case series of people hospitalised with COVID-19 in several countries found over-representation of people with diabetes. 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 More than a quarter of those admitted for COVID-19 in the UK had diabetes. 9 Just four studies, three from the UK, have compared risks in defined populations with and without diabetes, all of which found increased risks in those with diabetes for in-hospital and total deaths.…”
Section: Introductionmentioning
confidence: 99%
“…Lymphopenia, elevated D-dimer and other analytical signs of systemic inflammatory response syndrome (SIRS) has been observed [ 4 , 9 ]. In severe cases, individuals present severe bilateral interstitial pneumonia, commonly requiring admission in intensive care units (ICU) and mechanical ventilation [ 3 , 4 , 11 , 12 , 13 ]. Furthermore, SARS-CoV-2, like other coronaviruses, not only affects the respiratory tract but also the digestive tract, liver and heart [ 14 ].…”
Section: Introductionmentioning
confidence: 99%